2019
DOI: 10.1080/13504630.2019.1572502
|View full text |Cite
|
Sign up to set email alerts
|

On the Erasure of race in control culture discourse: a case study of Trayvon Martin’s role in the Black Lives Matter movement

Abstract: In this paper, we analyze an emergent cultural clash between: (a) how media outlets and other control culture institutions have portrayed events related to Black Lives Matter, and (b) the complex reality of Black Lives Matter movements as they have developed through embodied, intersectional, and always socially situated forms of direct collective action. In focusing specifically on American mainstream media coverage of the killing of Trayvon Martin, we argue that, given the history of white supremacy in Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Curiously, Bell (2015) stated that given the demographics of the area (20% African American, 23% Hispanic, 49% Caucasian, and 5% Asian) he looked like he fit in, yet not to Zimmerman. Fabregat and Beck (2019) found that the media's portrayal of Trayvon Martin as "guilty," maintains the social hierarchy and perceptions of race as "a problem" (Madison, 2015). The incident has been described by some as the catalyst for the BLM movement and certain sub-movements under the BLM movement (Smith, 2015).…”
Section: Trayvon Martin and Black Lives Mattermentioning
confidence: 99%
“…Curiously, Bell (2015) stated that given the demographics of the area (20% African American, 23% Hispanic, 49% Caucasian, and 5% Asian) he looked like he fit in, yet not to Zimmerman. Fabregat and Beck (2019) found that the media's portrayal of Trayvon Martin as "guilty," maintains the social hierarchy and perceptions of race as "a problem" (Madison, 2015). The incident has been described by some as the catalyst for the BLM movement and certain sub-movements under the BLM movement (Smith, 2015).…”
Section: Trayvon Martin and Black Lives Mattermentioning
confidence: 99%
“…When journalists act as “agents of racialization” (Drew, 2011, p. 355) – unconsciously or otherwise – this may redefine a movement in a manner that diminishes its credibility and ultimately public support, and thwarts legitimate efforts to reform the police. On this account, we implore media houses to recognize the need to confront racism and stereotyping among journalists and editors, who are implanted in a racially structured society (Fabrecat and Beck, 2019; Feagin and Ducey, 2019; Oliver, 2017a, b; Reskin, 2012). Journalists should be trained to identify their own implicit biases and understand that threat-related themes can, and do, perpetuate racism in news reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Our examination seeks to clarify whether the media defines the sociolegal principles of the movement as explained by movement leaders, or if media accounts use a lens that may blur the movement's purpose. The power that mass media has in framing, characterizing, and legitimizing social phenomena is “relevant and highly influential since it can shift attitudes and change ideas in relation to their audiences” (Fabregat and Beck, 2019, p. 762). This study aims to develop a clearer understanding of the nature of media representation, and uses news outlets in America and the UK to enable a comparative exploration of perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…As BLM gained space in the media, it became imperative to investigate the role of news media in determining individuals’ attitudes towards the movement. Portrayals of BLM were found to be often racialized, with numerous news outlets expressing explicit disapproval of protests, failing to contextualize the movement within the historical struggles of Black people, attributing blame for acts of violence to Black protesters, and framing peaceful protests derogatorily as riots (Fabregat and Beck 2019; Leopold and Bell 2017; Lane et al 2020). Research also revealed how media contextual and visual frames can affect individuals’ perceptions of protests.…”
Section: State Of the Artmentioning
confidence: 99%